The Size Effect in Malaysia’s Stock Returns - Syajarul Imna, Mohd Amin; Aisyah, Abdul-Rahman; Bakri, Abdul Karim (SpringerLink, 2024)
The size effect has been the most significant anomaly in stock price. Unlike developed stock markets, Malaysia’s market is smaller, less liquid, more volatile, prone to higher risk premiums and has higher cost of funds. These features could be attributed to informational inefficiency, high trading costs, and less competition. Nonetheless, investors have become interested in the Malaysian stock market for international diversification and potentially high returns. Thus, this research aims to examine the size effect in Malaysia’s cross-section of stock returns, involving 828 stocks listed in the FTSE Bursa Malaysia KLCI Index from January 2011 to December 2020. Fama–MacBeth-profitability regressions suggest that small firms and dividend payers perform better than large firms and non-dividend payers. Moreover, the small significant positive coefficient of lagged profitability suggests that Malaysian stock’s returns are not highly persistent. The findings would benefit investors, fund managers, and top management for portfolio diversification and risk management in Malaysia’s stock.